Image retrieval system for web / Normalyna Abdul Malek - Normalyna , Abdul Malek (2005)
The project title is Image Retrieval System for Web. This project is developed for the subject 'Projek Ilmiah Ta hap Akhir'. The system is a web based system. It is for the user to retrieve similar shape of images. The user for this system is any users who have internet connection and the administrator. The overall project cover the Introduction, Literature review, Methodology, System Analysis , System Design, System Implementation, System Testing and System Evaluation. This system is divided into two modules that will be developed by two people. Module 1 is to do image analysis and convert it into image data while module 2 covers the matching of image query from the system and the development of interfaces for the overall system. The research made was from internet resources, article or journal and also discussion with the supervisor and the moderator. The techniques used for this system is the Sobel Edge Detector, Reduced Chain Code, User Interface Design technique and the weighted Liechtenstein Distance. The system life-cycle model used is Iteration-and-Incremental Model. The main aim for this project is to achieve all of the Objectives at the end of the Image Retrieval System for Web development.